Beyond the Mountains of the Damned The War inside Kosovo - McAllester, Matthew (New York University Press, 2001)
Winner, Publishers Weekly Best Books of 2002, Non-FictionFor every survivor of a crime, there is a criminal who forces his way into the victim's thoughts long after the act has been committed. Reporters weren't allowed into Kosovo during the war without the permission of the Yugoslavian government but Matthew McAllester went anyway. In Beyond the Mountains of the Damned he tells the story of Pec, Kosovo's most destroyed city and the site of the earliest and worst atrocities of the war, through the lives of two men-one Serb and one Kosovar. They had known each other, and been neighbors for years before one visited tragedy on the other. With a journalist's eye for detail McAllester asks the great question of war: What kind of men could devastate an entire city, killing whole families, and feel no sense of guilt? The answer lies in the culture of gangsterism and ethnic hatred that began with the collapse of Yugoslavia
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: POLITICAL SCIENCE / World / European; Kosovo War, 1998-1999 -- Personal narratives, Albanian; Kosovo War, 1998-1999